The Students’ Perception towards English for Tourism and Hospitality in Terms of Task English Teaching Materials at Tourism Polytechnic of Makassar - Hasrul Hasrul; Haryanto Atmowardoyo; Nurdin Noni (Har Press Indonesia, 2021)
English is the language of the present age and it is also a global language. A recent estimation suggests that while around 375 million people speak English as their first language, another billion use it as a second language, or learning (Barančicová and Zerzová 2015). The role of teaching materials plays a significant part in the development of language. This study aimed to describe the students’ perception towards English for Tourism and Hospitality in terms of task English teaching materials. This research applied a quantitative-qualitative approach and descriptive method. The results revealed that students’ perception was in very good category. It concluded that the role of academics and lecturers in conducting task on learning materials is carried out based on the objective of vocational curriculum and the achievement of student competence has been progressing according to the mechanism. It is suggested that in developing and establishing teaching materials, developer, teachers, stakeholder should consider the target perception, and the difficulties faced by the lecturers may be manipulated by preparing a lot before teaching.